(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation. This article introduces the large class of Tetrapods, which are a large class of vertebrates. Representatives of this class are described as highly structured, highly developed tissues and organs, as well as information about the morphological, anatomical structure, origin and representatives of the class of amphibians belonging to this large class. Анатация. Эта статья знакомит с большим классом четвероногих, которые являются большим классом позвоночных. Представители этого класса описываются как высокоструктурированные, высокоразвитые ткани и органы, а также сведения о морфологическом, анатомическом строении, происхождении и представителях класса земноводных, относящихся к этому большому классу.